Studies on certain seminal plasma enzymes of crossbred bulls in relation to freezability of semen - MOHANTY, D N; ANSARI, M R (The Indian Journal of Animal Reproduction, 2023)
Semen from four bulls of poor freezability (SO % Post thawmotility) were analyzed for lactic dehyrogenase (LDH), reduced glutathione (GSH), alkaline phosphatase (ALP), acid phosphatase(ACP) and aspartate amino transferase (AST) in neat and post-thaw semen samples. The mean value of the enzymes and substratein the neat and post-thaw semen samples of good freezable bulls were estimated to be 111.19±3.54, 176.67±3.68 IU/L, 1.85±0.21,0.57±0.05 mmol/L, 241.67±7.65, 285.21±4.56 IU/L, 1043.63±11.05, 782.00±21.85 .IU/L and 43.73±1.15 and 52.11±1.88 IU/L.The corresponding values for poor freezable bull semen were, 76.85±4.84, 175.07±3.27 IU/L, 0.91±0.15, 1.17± 0.12 mmol/L,264.38±6.78, 324.38±7.45 IU/L, 948.75±9.30, 979.23±16.50 IU/L and 43.79± 1.30 and 53.11±1.79 IU/L, respectively. Significantdifferences (P
Keywords: Post thaw; enzymes; substrate; bull semen